(untitled) (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2026)
Traditionally, India’s traditional knowledge systems have always woven sustainability into them, and how communities have interacted with nature and how they have used resources and built their lives has been based on this sustainability. For centuries, ecological balance and resource and energy efficiency have been supported through indigenous practices such as step-wells for water conservation, organic farming methods, and Ayurveda-based health care. Now, however, industrialization and globalization have run so fast that almost all these proven approaches are pushed to the margin. The study argues that India’s traditional knowledge can be used as the basis of sustainability, but it uses bibliometric analysis to identify research trends and gaps. This study is undertaken through a qualitative approach, although it reviews the literature based on the data from Scopus and conducts bibliometric analysis for the research fields of IKS and sustainability. The study then shows that many of India’s traditional practices are nearly identical to modern sustainability goals. These focus on Zero Budget Natural Farming and sustainably produced textiles using natural dyes, as well as climate-responsive vernacular architecture, resource and low carbon footprints, and community-led conservation. However, given industrialization’s erosion of the indigenous knowledge systems and the absence of formal documentation, it is difficult to revive them on a large scale. Additionally, modern sustainability policies often favor traditional, nature-based approaches and delay their uptake in more mainstream sustainability policies.